Agrarian transition in the uplands of central Vietnam: drivers of market-oriented land-use and land-cover change - Saylor, Kirk, author; Leisz, Stephen, advisor; Galvin, Kathleen, committee member; Boone, Randall, committee member (Colorado State University. Libraries, 2019)
This study presents an analysis of changing land-use and land-cover in the North Central Coast region of Vietnam for the period in recent decades, during which rural upland communities have become partially integrated into commodity markets. Market integration has resulted from the extension of transportation network infrastructure under the East-West Economic Corridor (EWEC) project completed in mid-2006. This project has improved market connectivity and accessibility between rural and urban areas, creating flows of goods, information, and money induce agrarian transition and influence land-use / land-cover change processes. Analysis of satellite imagery over the last decade shows some signs of possible agricultural intensification along the Highway 9 corridor, while elsewhere in the study area a clear and consistent trendline cannot be ascertained. Confounding factors include usability of imagery, temporal gaps in collection, and the resolution of available and usable imagery. The pattern of changing land-cover emerging along Highway 9 is hypothesized to result from changing land rents, where lower transportation costs and higher agricultural prices increase the profitability of cash cropping, incentivizing local populations to engage in market-oriented production. Such a microeconomic response would be consistent with von Thünen's extrinsic theory of land rent, as well as the multi-scalar frameworks of teleconnections and telecoupling. These dynamics are explored at the village level through a spatially explicit agent-based model that simulates household decision-making using empirically-fitted rules, to better understand the process of transition from subsistence cropping to a mixed mode of production with cash cropping.
Keywords: land-cover; livelihoods; urban land teleconnections; land-use; agent-based modeling; telecoupling